The Psalms as Christian praise a historical commentary - Waltke, Bruce K. 1930-; Houston, J. M. 1922- (Grand Rapids William B. Eerdmans Publishing Company, 2019)
Intro -- Title Page -- Copyright -- Contents -- Preface -- 1. The Psalms as Christian Praise -- I. What: The Object of Praise, I AM -- II. Why Praise -- III. Who, Where, and When -- IV. How to Praise -- 2. Psalm 90: The Voice of Chastened Wisdom -- Part I. Voice of the Psalmist: Translation -- Part II. Commentary -- I. Introduction -- II. Exegesis -- Part III. Voice of the Church in Response -- I. Athanasius of Alexandria (c. 295-373) -- II. Augustine of Hippo (354-430) -- III. Gregory of Nyssa (c. 332-395) -- IV. Martin Luther (1483-1546) -- Part IV. Conclusion -- I. Canonical Context -- II. Message -- 3. Psalm 91: The Messiah's Invulnerability and Invincibility -- Part I. Voice of the Psalmist: Translation -- Part II. Commentary -- I. Introduction -- II. Exegesis -- Part III. Voice of the Church in Response -- I. Psalm 91 as Apotropaic -- II. Psalm 91 as Confessional in Temptation -- III. Jerome (342-420) -- IV. Augustine of Hippo (354-430) -- V. Bernard of Clairvaux (c. 1090-1145) -- Part IV. Conclusion -- 4. Psalm 92:You Are on High Forever, I AM! -- Part I. Voice of the Psalmist: Translation -- Part II. Commentary -- I. Introduction -- II. Exegesis -- Part III. Voice of the Church in Response -- I. The Origin of Psalm 92 for the Sabbath -- II. The Creation and the Eternal Sabbath -- III. The Church's Reception of a Sabbath Psalm -- IV. Augustine of Hippo (354-430) -- V. Medieval and Early Modern Poets -- VI. Living a Godly Life according to the Reformers -- Part IV. Conclusion -- 5. Psalm 93: I AM's Throne and the Earth Stand Firm -- Part I. Voice of the Psalmist: Translation -- Part II. Commentary -- I. Introduction -- II. Exegesis -- Part III. Voice of the Church in Response -- I. Augustine of Hippo (354-430) -- II. E. W. Hengstenberg (1802-1869) -- Part IV. Conclusion -- 6. Psalm 95: Venite -- Part I. Voice of the Psalmist: Translation.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books